A novel angiogenic pathway mediated by non-neuronal nicotinic acetylcholine receptors - Heeschen, Christopher (American Society for Clinical Investigation, 2002)
We have recently reported that nicotine has angiogenic effects, which appear to be mediated through non-neuronal nicotinic acetylcholine receptors (nAChRs). Here, we describe the endogenous cholinergic pathway for angiogenesis. In an in vitro angiogenesis model, increasing concentrations of the nonselective nAChR antagonist mecamylamine completely and reversibly inhibited endothelial network formation. Although several nAChR isoforms are expressed on endothelial cells (ECs), a similar inhibition was only obtained with the selective α7-nAChR antagonist α-bungarotoxin, whereas other selective antagonists did not result in significant inhibition of network formation. α7-nAChR was upregulated during proliferation, by hypoxia in vitro, and by ischemia in vivo. The nAChR-induced network formation was partially dependent on VEGF, was completely dependent on the phosphatidylinositol 3-kinase and mitogen-activated protein kinase pathways, and finally resulted in NF-κB activation. In vivo, pharmacological inhibition of nAChR as well as genetic disruption of α7-nAChR expression significantly inhibited inflammatory angiogenesis and reduced ischemia-induced angiogenesis and tumor growth. Our results suggest that nAChRs may play an important role in physiological and pathological angiogenesis. To our knowledge, this is the first description of a cholinergic angiogenic pathway, and it suggests a novel avenue for therapeutic modulation of angiogenesis.